2011
DOI: 10.1007/s11096-011-9489-y
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on the use of over-the-counter proton pump inhibitors for the treatment of GERD

Abstract: As defined by the treatment algorithm, the pharmacist should first confirm the diagnosis based on the presence of typical symptoms and secondly, as a result, rule out general practitioner referral. The third step focuses on the nature, severity and frequency of the symptoms--the patients who might have the highest benefit from a short course (14 days) of OTC PPIs are those with less than three episodes of heartburn and/or acid regurgitation per week. Patients who have three or more episodes per week can use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 63 publications
0
24
0
2
Order By: Relevance
“…Although our investigation was not designed to determine the specific causes of changes that we identify, several contributing factors may account for increases we observed, including the implementation of Medicare Part D, 10,34 changes to clinical guidelines, 35,36 and market dynamics, such as new therapies brought to market as well as patent expirations. 13,3740 …”
Section: Discussionmentioning
confidence: 99%
“…Although our investigation was not designed to determine the specific causes of changes that we identify, several contributing factors may account for increases we observed, including the implementation of Medicare Part D, 10,34 changes to clinical guidelines, 35,36 and market dynamics, such as new therapies brought to market as well as patent expirations. 13,3740 …”
Section: Discussionmentioning
confidence: 99%
“…Prospective clinical trials have shown the efficacy of these drugs taken on demand or intermittently on GERD management, with potential for cost reduction [17]. Although guidelines for OTC use [18, 436] suggest a short course (2 week treatment) of PPIs in patients with typical complaints (acid and/or regurgitation), and without alarm symptoms, great potential for misuse and/or overuse does exist. Major concerns include management of patients in whom symptoms persist despite acid suppression, appropriate administration, and the potential masking for more serious pathology, like malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…According to an internationally renowned gastroenterologist meeting on 2009, in Germany, the pharmacists should first confirm the diagnosis based on symptoms and secondly, rule in/out general practitioner referral [19]. However, our results indicated that pharmacists at Sharjah are not performing this job.…”
Section: Discussionmentioning
confidence: 65%